2019
DOI: 10.1242/jcs.230052
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of dendrite morphology and excitatory synapse formation by zDHHC15

Abstract: Protein palmitoylation is the most common post-translational lipid modification in the brain and is mediated by a family of 24 zDHHC enzymes. There has been growing interest in zDHHCs due to mounting evidence that these enzymes play key roles in the development and function of neuronal connections, and the fact that a number of zDHHCs have been associated with neurodevelopmental and neurodegenerative diseases. Loss-of-function variants in several zDHHCs, including zDHHC15, have been identified in patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 40 publications
0
36
0
Order By: Relevance
“…A zebrafish model for mutant zdhhc15b showed impairment in learning and memory behaviors in a T-maze test as well as reduced number of dopaminergic neurons and levels of TH and DAT proteins 44 . Zdhhc15 knockdown in cultured rat hippocampus neurons by shRNA was found to inhibit dendritic outgrowth and formation of mature spines 45 . Zdhhc15 -KO mice show normal number and projections of dopaminergic neurons in the nigrostriatal and mesolimbic pathways.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A zebrafish model for mutant zdhhc15b showed impairment in learning and memory behaviors in a T-maze test as well as reduced number of dopaminergic neurons and levels of TH and DAT proteins 44 . Zdhhc15 knockdown in cultured rat hippocampus neurons by shRNA was found to inhibit dendritic outgrowth and formation of mature spines 45 . Zdhhc15 -KO mice show normal number and projections of dopaminergic neurons in the nigrostriatal and mesolimbic pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Zdhhc15 , located at Xq13.3 in humans, encodes a protein palmitoyltransferase that is highly expressed in brain tissues 44 46 . Zdhhc15 knockdown was shown to reduce number and maturation state of dopaminergic neurons in zebrafish 44 and to decrease dendritic outgrowth, arborization, and spine maturation in cultured rat hippocampal neurons 45 . In vitro palmitoylation assays identified multiple ZDHHC15 substrates including PSD95 (postsynaptic density protein 95), CSP (Cysteine String Protein), DAT, GAP-43 (Growth Associated Protein 43), SNAP25b (Synaptosome Associated Protein 25, variant b), Sortilin, and Stathmin-2 47 .…”
Section: Introductionmentioning
confidence: 94%
“…To determine whether Zdhhc5 is involved in dendritic arborization and/or the formation of excitatory and inhibitory synapses, hippocampal neurons were transfected with eGFP plus the indicated constructs and immunostained for PSD-95 and gephyrin (faithful markers of excitatory and inhibitory synapses, respectively (Brigidi et al, 2015;Shah et al, 2019;Shimell et al, 2019); masking shown in Supplementary Figure 1A, B). While Zdhhc5 knockdown did not impact dendritic length ( Figure 1A), complexity ( Figure 1B Figure 1B for the creation of masks to quantify synaptic marker density).…”
Section: Zdhhc5 Promotes Excitatory Synapse Formation and Regulates Smentioning
confidence: 99%
“…ZDHHC15 belongs to a super-family of PATs that catalyze the attachment of palmitate to other protein substrates [26,27]. To identify the role of ZDHHC15 in protein palmitoylation in GSCs, we performed an ABE assay to identify proteins that are S-acylated by ZDHHC15 ( Figure 4A).…”
Section: Identi Cation Of Palmitoylation Proteins Mediated By Zdhhc15mentioning
confidence: 99%